Cardiac output decreases and systemic vascular resistance increases in newborns placed in the left-lateral position. - Paviotti, G; Todero, S; Demarini, S (J Perinatol, 2017)
OBJECTIVE: The objective of the study was to study the effect of short-term left-lateral position on cardiovascular parameters in hemodynamically stable newborns. STUDY DESIGN: Cardiac output (CO), stroke volume (SV), systemic vascular resistance index (SVRI) and heart rate (HR) were measured by electric velocimetry in hemodynamically stable newborns without respiratory support in the supine, left-lateral and back-to-supine positions, each kept for 10 min. RESULTS: Thirty-two newborns were enrolled, birth weight 2134 (1818 to 2460) g, gestational age 34.5±2.4 weeks. CO and SV decreased significantly from supine to left-lateral position (CO supine: 193.4 (168.0 to 229.6) ml kgmin; CO left-lateral: 172.0 (154.9 to 201.6) ml kgmin, P<0.0001; SV supine: 3.0 (2.7 to 4.0) ml; SV left-lateral: 2.7 (2.4 to 3.2) ml, P<0.0004). Conversely, SVRI increased in left-lateral position: SVRI supine: 18865±9244 dyns cm m; SVRI left-lateral: 21203±10059 dyns cm m, P<0.0001). All variables returned to the initial value when infants were back in the supine position. HR and blood pressure did not change. CONCLUSION: In stable infants, CO and SV decrease and SVRI increases, in left-lateral position.
Keywords: Blood Pressure; Cardiac Output; Female; Gestational Age; Heart Rate; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Italy; Male; Posture; Stroke Volume; Vascular Resistance

Making the first days of life safer: time for a new protocol? - Paviotti, G; Demarini, S; Verardi, G; De Cunto, A; Davanzo, R (J Perinatol, 2014)
Keywords: Beds; Female; Humans; Infant Care; Male